Which trade integration scheme can best help Sub-Saharan Africa develop and export more processed agricultural goods? - Douillet, Mathilde (International Food Policy Research Institute, 2011)
Trade integration of Sub-Saharan African (SSA) countries' agriculture is pointed out as a powerful driver of agricultural growth, especially if it increases processing of agricultural products. But there is no consensus on which negotiations for increased trade integration to put first. Static effects of regional and multilateral tariff reduction shocks are simulated with the Modeling International Relationships in Applied General Equilibrium computable general equilibrium model in order to compare them and test their coherence with the objective of enhanced value-added in agriculture. A new method is tested to treat existing data issues in the GTAP 7 database that usually lead to overestimations of gains from some trade integration.